Energetic Valorization of Cereal and Exhausted Coffee Wastes Through Anaerobic Co-digestion With Pig Slurry - Sousa, Sílvia; Duarte, Elizabeth; Mesquita, Marta; Saraiva, Sandra (Frontiers in Sustainable Food Systems, 2021)
In the past years, there has been steady growth in work relating to improve resource efficiency through waste minimization and bioenergy recovery to mitigate climate change. Agro-food industries produce large amounts of bio-waste, challenging innovative energetic valorisation strategies in the framework of circular economy principles. Anaerobic digestion technology is an interesting route to stabilise organic matter and produce biogas as a renewable energy source. This study involves continuous co-digestion of pig slurry, cereal and exhausted coffee wastes performed in a continuously stirred tank reactor, with an hydraulic retention times (HRT) of sixteen days under at mesophilic conditions (37 ± 1 °C). The experimental trials, were designed to include different cereal and exhausted coffee liquor (CECL) shares in the feeding mixture, corresponding to different pig slurry (PS) to cereal exhausted coffee liquor ratios (PS:CECL), respectively: 100:0 (T0), 90:10 (T1), 80:20 (T2) and 70:30 (T3), in terms of percentage of inlet feeding rate (v:v). The results obtained for the feeding rate (70:30) yield to the highest specific methane production (SMP = 341 mL .gVS-1) leading to 3.5- fold improvement in comparison with the reference scenario. The synergetic effect between the microbial consortia of pig slurry and the high carbon to nitrogen ratio (C/N) of cereal and exhausted coffee liquor explain the improvements achieved. The maximum SCOD reduction (84.0 %) due to the high content and soluble chemical oxygen demand to total chemical oxygen demand ratio (SCOD/TCOD) corroborate the results achieved. The digester stability, evaluated by specific energetic loading rate, was below the limit (0.4 d−1). Results from ANOVA showed a significant effect of CECL on the resulting GPR and SMP values. Additionally, Tukey's ‘Honest Significant Difference’method, confirmed statistically significant differences between the trials T3-T0, T3-T1, T3-T2 and T2-T0. Thus, co-digestion of pig slurry and of cereal and exhausted coffee liquor seems to be a promising approach for bioenergy recovery and promoting biowastes circularity.